AN ANALYSIS OF TEACHERS’ NON-VERBAL COMMUNICATION IN EFL CLASSROOM AT SMP NEGERI 3 BANJAR - Indrawan, I.P.; Nitiasih, P.K.; Piscayanti, K.S. (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2017)
This study was aimed at (1) analyzing kinds of non-verbal communications used by English teachers during the teaching and learning process, (2) revealing what kinds of teachers’ non-verbal communications affect students’ motivation during the learning process in the classroom, (3) discussing the contribution of non-verbal communications in English education. This study was a descriptive qualitative study conducted at SMPN 3 Banjar. The data were collected by video recording, questionnaire administration, and interviewing. There were 2 English teachers involved as the subject of this research, and 40 students of eighth grade in different classes were involved.  The results of the study indicate teachers’ non-verbal communication in SMPN 3 Banjar meets the seventh kinds of non-verbal communication proposed by Burgoon, Buller, and Woodall, (1994) as cited in Birjandi and Nushi (2014). It was also found that there are some kinds of non-verbal communication that affect students’ motivation, namely facial expression, body movement, gestures, proxemics (proximity), haptics (touch), eye contact, and paralanguage. Gestures and paralanguage are considered as non-verbal communication that gives contribution to English education.